Grouper TRIM23 exerts antiviral activity against iridovirus and nodavirus - Zhi, Linyong; Wang, Wenji; Zheng, Jiaying; Liu, Shanxing; Zhou, Sheng; Qin, Qiwei; Huang, Youhua; Huang, Xiaohong (Frontiers in Immunology, 2022)
TRIM (tripartite motif) proteins have been demonstrated to exert critical roles in host defense against different microbial pathogens. Among them, TRIM23 acts as an important regulatory factor in antiviral immune and inflammatory responses, but the roles of fish TRIM23 against virus infection still remain largely unknown. Here, we investigated the characteristics of TRIM23 homolog from orange spotted grouper (Epinephelus coioides) (EcTRIM23). EcTRIM23 encoded a 580 amino acid peptide, which shared 93.1%, 89.73% and 86.36% identity with golden perch (Perca flavescens), zebrafish (Danio rerio) and human (Homo sapiens), respectively. The transcription levels of EcTRIM23 were significantly up-regulated in response to Singapore grouper iridovirus (SGIV) and red-spotted grouper nervous necrosis virus (RGNNV) infection. EcTRIM23 overexpression in vitro significantly inhibited RGNNV and SGIV replication, evidenced by the delayed cytopathic effect (CPE) progression and the decreased expression of viral core genes. EcTRIM23 significantly increased the expression levels of interferon (IFN) related signaling molecules and pro-inflammatory cytokines, as well as the promoter activities of IFN and NF-κB, suggesting that EcTRIM23 exerted antiviral function by positively regulating host IFN response. Exogenous EcTRIM23 exhibited either diffuse or aggregated localization in grouper cells. After co-transfection, TANK binding kinase 1 (TBK1), TNF receptor associated factor (TRAF) 3 and TRAF4, TRAF5 and TRAF6 were found to interact with EcTRIM23 in grouper cells. Moreover, these proteins could be recruited and co-localized with EcTRIM23 in vitro. Together, our results demonstrated that fish TRIM23 exerted antiviral activity against fish viruses by interacting with multiple host proteins to regulate immune responses.